Nilai Tambah Produk Agroindustri Keripik di Kota Kefamenanu (Studi Kasus Usaha Keripik Paman Sularso) - Joka, Umbu (Musamus University, 2022)
The research on chips business aims to determine the added value of chips (banana and cassava) processing business in Kefamenanu City. The data analysis method used in this research is descriptive qualitative analysis method, and added value analysis. The sample is the owner of his own business, namely Uncle Sularso. The results showed that the business of chips (bananas and sweet potatoes) in 2021. The added value obtained from processing sweet potato chips in one year is Rp. 3,600. This added value is obtained from reducing the value of the product with the price of raw materials and the value of other inputs. The value added ratio is a comparison between the added value and the product value. The added value ratio obtained is 14.0625 percent. This means that the processing of bananas and sweet potatoes into chips provides an added value of 14.0625 percent of the product value. The added value obtained from processing banana chips in one is Rp 5,077. This added value is obtained from reducing the value of the product with the price of raw materials and the value of other inputs. The value added ratio is a comparison between the added value and the product value. The value added ratio obtained is 22 percent.